Delineating a case system: How many cases are there in Standard Goan Konkani – and why? - Peterson, John; Mopkar, Govind (Lingua Posnaniensis, 2024)
In the present study we analyze the case system of Standard Goan Konkani, an Indo-Aryan language spoken in western India. We first analyze the individual markers which fit our definition of case markers and discuss how these differ from and/or overlap functionally with other case markers. We then present a detailed description of two further case markers which, although quite common, to our knowledge have not been discussed in previous works on Konkani, namely the selective and the elative, and show how these forms, despite their transparent etymologies as case stacking of the inessive case and either the genitive or the ablative, cannot be viewed as case stacking in the modern language. With this, we argue that Konkani can best be described as having 13 productive cases, although other analyses are possible, depending on researchers’ theoretical and practical preferences.